STUDENTS' PERCEPTIONS OF ONLINE-BASED LEARNING IN JUNIOR HIGH SCHOOL - Marina Putty Ariestian; Kusrin Kusrin (IKIP Siliwangi, 2022)
In this era of the Covid-19 pandemic, online-based learning is the best solution for the learning process in education. This study aims to describe students' perceptions of online learning at the junior high school level. This research uses descriptive qualitative research method. The population in this study were 18 junior high school students and a sample of 12 students was obtained from students who filled out a questionnaire randomly. The 12 students consisted of 9 female students and 3 male students. The sample was given a perception questionnaire made on Google Form. Data were analyzed descriptively from questionnaires, distribution tables and presented data in the form of diagrams. The results showed that 81% of students were able to access online learning well, 84% of students were able to learn independently in online learning, 71% of students thought that online learning was effective, and 54% of students thought that communication between teachers and students went well in online learning. Students' perceptions of online-based learning in Junior High Schools get positive response results. Keywords: Student Perception, Online-Based Learning, Junior High School